Contact chemical burn of the hand caused by xylene: A case report. Issue 3 (8th May 2020) - Dewar, Zachary Ewan; Christiansen, Gregory
Abstract: The use of household cleaners during non‐commercial cleaning applications is a very common task, and the chemical makeup of the cleaning solutions vary as much as their applications do. Although most users of these products follow the written safety directions and are generally careful with their use, it is not uncommon for users to suffer toxicologic effects of these cleaners without proper protective equipment. In this case report, we describe an unusual chemical burn pattern to the hand of a young female patient after prolonged exposure to a xylene‐containing product without proper chemical‐resistant gloves. Fortunately, with prompt recognition, and urgent referral for burn treatment, the patient underwent a successful debridement of the burn and suffered minimal functional impairment.